Analyzing the Relationship Between Education Budget Allocation and Gross Participation Rate in West Java (2018–2022) - Saiful Almujab; Yosi Hurifatul Hasanah (STAI Hubbulwathan Duri, 2025)
This study investigates the impact of education budget allocations on the gross enrollment rate (GER) in the cities and districts of West Java, Indonesia. Additionally, it explores underlying factors that may be impeding educational transformation in the region. A panel dataset was compiled, covering 27 cities and districts in West Java over a five-year period (2018–2022). The data included annual percentages of education budget allocations and corresponding GER values. The analysis employed the Random Effects Model for panel data regression to evaluate the relationship between the variables. The regression analysis revealed a negative, statistically insignificant relationship between education budget allocation and the gross enrollment rate. The findings suggest that increases in education budgets have not corresponded with improvements in enrollment rates across the region. These results indicate that higher budget allocations alone do not guarantee better educational outcomes. The study raises concerns about inefficiencies in budget utilization and suggests the presence of systemic or structural issues within the education system that may be limiting the impact of increased funding.